2019
DOI: 10.3390/en12142778
|View full text |Cite
|
Sign up to set email alerts
|

Developing Interventions for Scaling Up UK Upcycling

Abstract: Upcycling presents one of many opportunities for reducing consumption of materials and energy. Despite recent growth evidenced by increasing numbers of practitioners and businesses based on upcycling, it remains a niche activity and requires scaling up to realise its potential benefits. This paper investigates UK household upcycling in order to develop interventions for scaling up upcycling in the UK. Mixed methods were used in four stages: (a) Interviews to gain insights into UK upcycling; (b) a survey to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 137 publications
0
34
0
Order By: Relevance
“…The topic of research under study is dynamic and it is observed that the contributions are adapted to its rapid evolution [131]. In relation to the new lines of research on sustainable management, the keyword "upcycling" has emerged in response to the use of recyclable materials to create objects with a greater value than the initial [132,133], and its application in teaching and learning in HE [134][135][136]. In addition, among the concepts that arise associated with the DT of HE, the "digital community" stands out, in relation to groups of individuals and institutions organized virtually around a series of specific interests, whose interactions occur on the Network (discussion forums, email groups, chats, or peer-to-peer systems) [137].…”
Section: Keyword Analysismentioning
confidence: 99%
“…The topic of research under study is dynamic and it is observed that the contributions are adapted to its rapid evolution [131]. In relation to the new lines of research on sustainable management, the keyword "upcycling" has emerged in response to the use of recyclable materials to create objects with a greater value than the initial [132,133], and its application in teaching and learning in HE [134][135][136]. In addition, among the concepts that arise associated with the DT of HE, the "digital community" stands out, in relation to groups of individuals and institutions organized virtually around a series of specific interests, whose interactions occur on the Network (discussion forums, email groups, chats, or peer-to-peer systems) [137].…”
Section: Keyword Analysismentioning
confidence: 99%
“…Other quite recurring types of waste are plastics [86][87][88][89][90], metal cans [91][92][93], and batteries [94][95][96], besides the purchase of green products [97][98][99] or electronic products [100,101], considering waste management impacts the acquisition phase too.…”
mentioning
confidence: 99%
“…The absence of infrastructure and environmental education resulted in a relatively low level of environmental knowledge of apparel products among Chinese consumers, which in turn did not lead to positive intentions toward sustainable fashion consumption behaviors. In the UK [81] and the US [4,82], however, a higher eco-consciousness and a favorable value shift toward reuse and recycling increased the positive intentions toward clothing for sustainable consumption. The UK and the US are leaders in both social and environmental sustainability [16].…”
Section: Country Differences In Sustainable Apparel Consumptionmentioning
confidence: 99%
“…That is, since different structures of economic and cultural norms affect individual consumers' values, different perceptions, and criteria when they decide to buy apparel products, consequently influencing behavioral intentions [85]. According to the cultural differences discovered in pro-environmental and sustainable consumer behavior in the literature [4,81,82,[85][86][87], we also explore the question of the influence of different countries and cultures in the way they experience biodiversity. Previous studies suggest that across cultures eco-friendly and sustainable consumption behavior is influenced by environmental consciousness and by values evaluated in conjunction with other variables.…”
Section: Country Differences In Sustainable Apparel Consumptionmentioning
confidence: 99%